X marks the spot, maybe [GPS navigation]. - Bretz, E.A (IEEE spectrum)
Navigation has long been considered an art form best practiced by experienced sailors. But today, thanks to the multitude of affordable, hand-held, Global Positioning System receivers on the market, almost anyone can be a navigational Magellan. The US Department of Defense (DOD) is at an advantage: it reserves for its own use the most accurate form of geolocation available, which puts X within a meter or two of the spot. Meanwhile, civilian users have to be content with X at best 100 meters from the spot, thanks to deliberate degradation of the signal by the DOD. That may soon improve. Pressure for more accurate civilian signals is being generated by the explosive growth in the numbers of users and applications of the Global Positioning System (GPS), known in the United States as Navstar GPS. Part of the demand stems from changes prompted by CPS in the way some industries operate. As the demand for improved service grows, so does the need for more accuracy. Greater accuracy translates into a call for additional signals. Two extra civilian carrier frequencies are coming with the next batch of satellites (known as Block IIF) that are now in the design and construction phase and scheduled for launch beginning in 2003. The additional signals will put nonmilitary users as close as 10 meters or so to the spot by taking advantage of the multiple frequencies to correct positioning errors that occur naturally when only one signal is available. Plus, new signals won't be intentionally degraded by DOD